A TRANSNATIONAL EXCHANGE MECHANISM AMONG MOLDOVAN MIGRANTS IN THE PARISIAN REGION: EXPLORING THE “POST OFFICE OF MOLDOVA” - Dorina Rosca (Economy and Sociology, 2023)
This article delves into the phenomenon of material goods circulation in the context of international migration, specifically looking at the exchange of parcels between Moldovan immigrants in the Paris region, France, and their kin, friends, and acquaintances in Moldova. The analysis uses field data collected during an ethnographic study conducted in 2017 within the Moldovan immigrant community in Paris. It moves beyond the limitations of push-pull theories that focus solely on one-way material circulation from immigrants to their home country families or only on the economic implications of remittances.